Development and Harm of Liriomyza Sativa Blanchard leaf--mining Flies - A.N.Jumayeva; U.А.Isashova; М.K.Rakhmonova; A.R.Anorbayev (Indonesian Journal of Innovation Studies, 2019)
This article is focused on the continuation of the development of miners that are considered to be main pests of vegetable plants. Due to the gathered information, it was identified that in an optimal condition, a generation of a leaf-mining fly (Liriomyza sativa B) develops in 17.5 days. Also, we have identified the level of its harm to vegetable plants.